Criminological Views Against Abuse Narcotics by Child - Vicki Dwi Purnomo; Trisno Raharjo; Syukron Abdul Kadir (Formosa Journal of Social Sciences (FJSS), 2023)
The causes of children abusing narcotics in terms of criminology. This writing uses empirical research methods with a case approach, this approach researchers will get information from various aspects of the actual issue. Factors that cause narcotics abuse by children are influenced by various factors including personal factors, family factors, environmental factors, certain group or organizational factors, economic factors, and vulnerable population factors. Efforts that can be made in overcoming narcotics abuse by children are divided into two, namely preventive or repressive efforts or prosecution. Preventive efforts are efforts made with preventive activities carried out by the authorities in this case the police in order to minimize the occurrence of Narcotics Abuse by children